Ilizarov External Fixator Versus Internal Fixation for Ankle Joint Arthrodesis in Diabetic Charcot Neuroarthropathy - Yontar, Necip Selcuk; Öğüt, Tahir (Cerrahpaşa Medical Journal, 2022)
Objective: This study aims to evaluate the patients with Charcot neuropathy and look for differences in fusion rate, limb salvage rate, and complications following external fixation and internal fixation used in tibiotalar/tibiocalcaneal arthrodesis. Methods: 12 patients were identified and evaluated for the rate of limb salvage, complications, union at arthrodesis site, and clinical results based on the modified American Orthopaedic Foot and Ankle Society scale. Results: After an average follow-up of 70.9 months, we found 100% limb salvage rate; of the 12 patients, 8 had an osseous union at the arthrodesis site. Using the modified American Orthopaedic Foot and Ankle Society scale, we calculated a mean score of 79.4 (range, 75-84) points in the external fixation group and 79.2 (range, 71-85) points in the internal fixation group (P > .05). The results were excellent in 5 patients (100%) in the external fixation group and were excellent in 5 patients (71.4%) and good in 2 patients (28.6%) in the internal fixation group. Three patients in the external fixation group had pin tract infection that resolved with appropriate treatment. On the other hand, 1 patient in the internal fixation group experienced a tibial stress fracture that required revision nailing. Conclusion: It is possible to obtain 100% limb salvage regardless of the fixation method with an individualized treatment plan in patients with Charcot neuropathy-related ankle involvement. Cite this article as: Yontar NS, Öğüt T. Ilizarov external fixator versus internal fixation for ankle joint arthrodesis in diabetic charcot neuroarthropathy. Cerrahpaşa Med J. 2022;46(2):101-103.